Canva Interactive Media Increases Elementary Students Learning Interest: Media Interaktif Canva Meningkatkan Minat Belajar Siswa Sekolah Dasar - Safitri, Suci; Rahman, Abdul; Nuraini Nuraini; Zulnuraini, Zulnuraini; Isnayanti, Andi Nur (Academia Open, 2026)
General Background: The integration of digital technology in education has shifted learning practices toward interactive and visually supported approaches aligned with the demands of the industrial revolution 4.0. Specific Background: In elementary education, learning interest remains a critical factor, yet conventional teaching methods often lead to low student engagement, particularly in IPAS learning contexts. Knowledge Gap: Previous studies largely address digital media broadly, with limited focus on Canva-based interactive media tailored to elementary student characteristics. Aims: This study aims to examine the use of Canva-based interactive learning media in increasing learning interest among fourth-grade students at SD Inpres Perumnas Palu. Results: Using a quantitative experimental design with control group pretest-posttest, the findings show an increase in learning interest in both groups, with a higher rise in the experimental class (18.95 to 28.95) compared to the control class (16.83 to 25.87), supported by a significance value of <0.001. Novelty: The study provides a contextual application of Canva interactive media adapted to elementary student characteristics within IPAS learning. Implications: The findings indicate that interactive digital media such as Canva can support student engagement, encourage active participation, and contribute to more dynamic classroom environments when combined with appropriate teaching strategies. Highlights • Canva-based visuals stimulate higher classroom participation during IPAS lessons. • Experimental group shows greater score increase compared to conventional teaching. • Interactive design supports student attention and learning involvement. KeywordsInteractive Learning Media; Canva Application; Learning Interest; Elementary Education; Digital Learning